Compliance e mercado da arte: uma análise do sistema de regulação multifacetado em transações de obras artísticas - Pontes, Ílina Cordeiro de Macedo (2019)
Money laundering, museum thefts, terrorism financing and counterfeiting are constantly conveyed in headlines. It is clear that the art market is remarkably used as a medium for illicit practices. The reasons for this phenomenon remain on the art market characteristics, as well as the absence of an effective public regulation. However, the identification of code of ethics, guidelines, among other documents, raised the hypothesis that compliance appears as a self-regulation tool in this market. In order to verify it, the hypothetical-deductive method was used, as well as qualitative and documentary research, based on secondary sources. The research procedure was based in three steps, each one with specific objectives. Firstly, it was analysed the structure of the actors which make part of this economic sector, as well as the reasons of its susceptibility for criminal practices. Secondly, the meaning of compliance was pursued. Then, it proved to be much more complex than its gramatical definition, as a multifaceted regulating structure which comprises both public and private legal orders. Finally, the compliance in this market was analysed from five diferente documents, in order to identify the essential points of a compliance program in the art market, and especially in Brazil.